077 Standardising simulation support: improving quality by planning. (5th November 2017) - Gay, Christopher
Abstract : Background: Simulation Based Education is a term that covers a very broad range of possibilities, and even wider range of resource, staffing and equipment implications. At the Hull Institute of Learning and Simulation (HILS) we developed a range of documentation to support successful simulation activity planning. HILS have 13 high fidelity simulators, and current knowledge and experience is spread across of team of more than 8 staff, so it became important to be able to assign the right support to the right event. Project description: Three key documents were created to support simulation: Simulation Planning Tool – a user friendly form to quickly gather the faculty needs before the event – also serves a discussion point about how they'd like to run the simulation Simulation Use form- lead faculty fills in to document simulator use and highlight responsibility of care for equipment – also contributes towards monthly simulation usage figures Simulation Maintenance Form –technician logs condition of simulator to identify cleaning or repair needs If possible, all three of these forms are filled out per event. Outcomes The documents have resulted in- Simulation Planning Tool- in increased awareness for faculty of what options are available to them within simulation, such as video recording and in debriefing, as well as a positive impact of faculty and simulation team communication. Simulation Use form- has helped reinforce the expensive nature of simulators and provided vital usage statistics for demonstrating simulator return on investment Simulation Maintenance Form –has enabled recurring problems with simulators to be highlighted and remedied, as well as promoting a culture of care for the equipment Conclusions: Simulation faculty can rapidly change, but by introducing standardised documentation it can assist the incremental build-up of knowledge and experience across a team, ensuring more consistent support and therefore simulation activity that can focus on the learner rather than the range of logistical challenges that need to be overcome to make it happen.